«Sociology» and «History of Sociology» for «Social work»: to the conceptualization of sociological component education - Сорока, Ю. Г.; Борисов, Р. І. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2021)
The article proposes a review and substantiation of the conceptual foundations of the study of sociology within the framework of the Educational Programme «Social work» at the sociological faculty of V. N. Karazin Kharkiv National University. The relevance of such a statement of the problem is associated with a discussion of the definition of the purpose of this educational program and its features, which consist, in particular, in in-depth training in sociology. Based on the characteristics and features of the educational program, the article formulates the initial provisions that guide the conceptualization of its sociological component, in particular, the nature of the discipline, the main direction of the sociological component of training, its central concept and requirements for the structure. Thematic priorities in teaching courses in «Sociology» and «History of Sociology» within the framework of the Social Work educational program have been determined. The substantiation of the conceptual foundations and thematic structure of the course «History of Sociology» is presented. In particular, the main questions have been identified that the course should answer and, accordingly, the historical and sociological material was selected. Reorientation from methodological to ontological features of sociological theorizing is substantiated. A method of paradigmatic unification of sociological concepts for effective understanding by students of the essence of sociological thinking has been chosen. The main sections of the course are characterized and its thematic structure is presented. The thematic plan of the course «Sociology» as an element of the sociological component of the educational program «Social work» is proposed and its differences from the thematic structure of the sociology course for non-core audiences are argued. By referring to the psychological, pedagogical and didactic aspects, the author describes the introduction of an appropriate system of methods of teaching, learning, support and assessment of educational activities within the framework of the courses «Sociology» and «History of Sociology».